Analisis Kesalahan Penggunaan Kata Bantu ä¸¤ [LiÇŽÅ‹] danäºŒ [Éš] dalam Pembelajaran Bahasa Mandarin - Dini, Citra Hardianti; Burhanuddin, Burhanuddin; Adys, Himala Praptami (Interference: Journal of Language, Literature, and Linguistics, 2021)
Abstract. This study aims to classify the types of errors made by students of class XI SMA Islam Athirah 2 Makassar in the use of auxiliary words ä¸¤ [liÇŽÅ‹] and äºŒ [Éš] in Mandarin. This type of research is descriptive quantitative. Data were collected using a test using the auxiliary words ä¸¤ [liÇŽÅ‹] and äºŒ [Éš]. The analytical method used is the error analysis proposed by Ellis in Tarigan. The population of this study were all students of class XI SMA Islam Athirah 2 Makassar which consisted of 9 students as well as the research sample using the total sample technique. This research data comes from the analysis of the use of the auxiliary words ä¸¤ [liÇŽÅ‹] and äºŒ [Éš]. The results of data analysis show that there are 67 errors in the use of auxiliary words ä¸¤ [liÇŽÅ‹] and äºŒ [Éš]. There were 33 errors in the use of auxiliary words ä¸¤ [liÇŽÅ‹] or 49.25% which were in the poor category and 34 errors in the use of auxiliary words äºŒ [Éš] were 34 total errors or 50.75% which were in the under category error level.